2016
DOI: 10.1111/cpf.12376
|View full text |Cite
|
Sign up to set email alerts
|

Acute resistance exercise with blood flow restriction in elderly hypertensive women: haemodynamic, rating of perceived exertion and blood lactate

Abstract: In comparison with high-intensity resistance exercise, low-intensity resistance exercise with BFR can elicit: (i) same haemodynamic values during exercise; (ii) lower rating of perceived exertion; (iii) lower blood lactate; (iv) higher haemodynamic demand during the rest intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 30 publications
4
62
0
3
Order By: Relevance
“…Other populations included resistance‐trained adults, adults with musculoskeletal or soft tissue injuries, older adults, or adults with hypertension. There were far more studies (26 of 52) examining only male participants, 17,24,25,30,32‐38,41‐43,46,48,50‐59 compared with just 8 of 52 examining only female participants, 40,49,60‐65 leaving 18 studies examining both of these genders 8,19,20,39,44,45,47,66‐75 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other populations included resistance‐trained adults, adults with musculoskeletal or soft tissue injuries, older adults, or adults with hypertension. There were far more studies (26 of 52) examining only male participants, 17,24,25,30,32‐38,41‐43,46,48,50‐59 compared with just 8 of 52 examining only female participants, 40,49,60‐65 leaving 18 studies examining both of these genders 8,19,20,39,44,45,47,66‐75 …”
Section: Resultsmentioning
confidence: 99%
“…Sixteen of the 52 included studies applied multiple different cuff pressures as a means of comparing acute responses or chronic adaptations to different applied pressures 17,20,31,32,36,39,43,44,48,54,67,68,70,72,73,75 . Among the remaining 36 studies using a single individualized pressure for their application of BFR, 13 studies used 80% AOP/LOP, 24,37,40,49,50,57,61,62,64‐66,71,74 7 studies used 60% AOP/LOP, 8,33,34,38,46,52,56 5 studies used 50% AOP/LOP, 25,41,42,59,60 4 studies used 100% AOP, 47,51,58,63 4 studies used 40% AOP/LOP, 19,30,45,69 and 3 studies used 30% AOP 35,53,55 . The technique and postures used to determine each of these individualized restriction pressures was similarly variable.…”
Section: Resultsmentioning
confidence: 99%
“…Still, the pressure was relieved between the three attempts in each test (isometric and dynamic test). One might speculate that the repeated maximal effort might lead to an accumulation of blood lactate (Pinto et al, 2018) and cause peripheral fatigue using BFR. However, the results do not support the speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the chronic effects of BFR training (typical 20-30% of 1RM) have demonstrated similar muscle hypertrophy, accompanied by both similar and lower increases in muscle strength compared traditional strength training approaches (>65% of 1RM) (Abe, Kearns, & Sato, 2006;Takarada, Sato, & Ishii, 2002). Acute effects of BFR have demonstrated increased muscle activation and recruitment of type II motor units (Moore et al, 2004;Takarada, Takazawa, Sato et al, 2000), lower blood lactate and perceived exertion, in addition to increased muscle protein synthesis and anabolic signaling (Boeno et al, 2018;Fatela, Reis, Mendonca, Avela, & Mil-Homens, 2016;Pinto, Karabulut, Poton, & Polito, 2018;Wernbom, Jarrebring, Andreasson, & Augustsson, 2009). However, acute effects of BFR have demonstrated reduced performance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Senam terbukti menurunkan laju peredaran darah pada lansia terhadap systole, distole, dan denyut nadi serta stroke volume. 13 Kegiatan lain yang disukai oleh Lansia adalah bercerita, apalagi menceritakan perjalanan hidupnya life review reminiscence. Metode ini efektif bagi lansia untuk mengurangi dimensia, 14 akan tetapi tidak semua suka akan metode ini karena beda tipe kepribadian.…”
Section: Pendahuluanunclassified